PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN UKURAN PERUSAHAAN SEBAGAI ALAT PREDIKSI PERINGKAT OBLIGASI - Wahyu Dian Tri Handayani; Cahyani Nuswandari (Jurnal Akuntansi dan Pajak, 2023)
Investment in the capital market is an investment in the financial sector, where this type of investment has a high risk compared to other investments but investment in the financial sector will provide high returns for investors. Bonds are issued by companies because companies need alternative sources of financing in the long term, therefore investors need to pay attention to these things before starting to invest in bonds because they have a low level of risk. This type of research uses hypothesis testing which explains the nature and relationship between variables which aims to explain the causal relationship between the independent and dependent variables through the data analysis process and the population in this study are manufacturing companies that issue bonds in 2017-2021. The results showed that profitability and firm size had a significant positive effect on bond ratings, liquidity and leverage had no effect on bond ratings.